Social accounting practices among Kenyan firms: An empirical study of companies quoted at Nairobi Securities Exchange - Mwasa, Ishmail; Sira, F. N.; Leonard, Maina (My University, 2014)
Profit and shareholders wealth maximization have for long dictated accounting and reporting practices, the concern for the social costs and the benefits of the business practices have given rise to the need for environmental and social accounting. The Significance of the study was to determine how companies are reporting positive and negative externalities to the society. The main objectives of the study was to establish the most popular themes of social accounting in Kenya, determine how and location for disclosure of social accounting information. The population of the study was fifty seven companies quoted in NSE and longitudinal study was carried from 2008-2010. Census method was used to collect data. Secondary data was collected from published annual financial statement of all listed companies. The population of companies is categorized into four market segment, Content analysis and descriptive analysis was used in analyzing data. It was established in the year 2008, companies practicing social accounting were 72%, while 2009 were 75% and in 2010 were 81%. It was also established that community involvement and environment themes was leading in practice of social accounting. Finally, it was established that companies prefer non-monetary form over monetary form of presentation and also they prefer using separate location to using chairman’s report in annual reports.
Keywords: Social Accounting; Environmental Accounting; Nairobi Security Exchange